Searching for New Regulatory Frameworks for the Intermediate Financial Market Structure in Post-Crisis Asia - Sayuri Shirai (Asian Development Bank Institute (ADBI), 2001)
In Asia, commercial banks are already playing an important role in the corporate bond market as issuers, underwriters, investors, and guarantors. This reflects banks' dominance of their financial markets, their high reputation, and the informational advantages they enjoy. Thus, banks should be encouraged to foster corporate bond market development and pursue a complementary role. Such a financial landscape can be characterized as an “intermediate financial market structure,” which lies somewhere between a bank-dominated financial structure and a full-fledged capital market-based financial structure.
hdl:11540/4129
Keywords: 330